2013
DOI: 10.1523/jneurosci.4384-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

ACR-12 Ionotropic Acetylcholine Receptor Complexes Regulate Inhibitory Motor Neuron Activity inCaenorhabditis elegans

Abstract: Heterogeneity in the composition of neurotransmitter receptors is thought to provide functional diversity that may be important in patterning neural activity and shaping behavior (Dani and Bertrand, 2007; Sassoe-Pognetto, 2011). However, this idea has remained difficult to evaluate directly due to the complexity of neuronal connectivity patterns and uncertainty about the molecular composition of specific receptor types in vivo. Here we dissect how molecular diversity across receptor types contributes to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 35 publications
2
59
1
Order By: Relevance
“…2 DD neurons receive cholinergic synaptic inputs, and express acetylcholine receptor subunits, including ACR-12, 16 in their dendrites. In L1 DD neurons, OIG-1 prevents remodeling of ACR-12.…”
Section: Factors That Regulate the Timing Of Dd Remodelingmentioning
confidence: 99%
“…2 DD neurons receive cholinergic synaptic inputs, and express acetylcholine receptor subunits, including ACR-12, 16 in their dendrites. In L1 DD neurons, OIG-1 prevents remodeling of ACR-12.…”
Section: Factors That Regulate the Timing Of Dd Remodelingmentioning
confidence: 99%
“…The nicotinic AChR subunit ACR-12 is a constituent of GABA neuron iAChRs. ACR-12::GFP clusters localize opposite ACh release sites and relocate appropriately during developmental remodeling, suggesting that these clusters report mature postsynaptic structures (Petrash et al, 2013;He et al, 2015). We examined the distribution of ACR-12:: GFP in the dorsal nerve cord where the majority of chemical synaptic inputs to VD neurons occur (VD synaptic contacts with muscles are exclusively ventral) (White et al, 1986).…”
Section: Unc-3 Transcriptional Regulation Coordinates Cholinergic Synmentioning
confidence: 99%
“…Our finding that other subunits required for the levamisolesensitive nAChR (Fleming et al 1997;Culetto et al 2004) are not required for EHC suggests that UNC-63 is acting in a different receptor to mediate EHC. We tested the only additional receptor currently known to include the UNC-63 subunit, the neuronal ACR-2 receptor (Jospin et al 2009;Petrash et al 2013), and found that loss of that receptor, through loss of function in the acr-2 gene, did not alter sensitivity to EHC. These results suggest that UNC-63 is likely to act in an as yet unidentified receptor(s) to mediate EHC.…”
Section: Cholinergic Signalingmentioning
confidence: 99%
“…We tested the only additional receptor currently known to include the UNC-63 subunit, the neuronal ACR-2 receptor (Jospin et al 2009;Petrash et al 2013), and found that loss of that receptor, through loss of function in the acr-2 gene, did not alter sensitivity to EHC. These results suggest that UNC-63 is likely to act in an as yet unidentified receptor(s) to mediate EHC.…”
Section: Cholinergic Signalingmentioning
confidence: 99%
See 1 more Smart Citation